Visceral leishmaniasis in Ethiopia: an evolving disease. - Samson Leta; Thi Ha Thanh Dao; Frehiwot Mesele; Gezahegn Alemayehu (Public Library of Science (PLoS), 2014)
Visceral leishmaniasis (also known as kala-azar) is classified as one of the most neglected tropical diseases. It is becoming a growing health problem in Ethiopia, with endemic areas that are continually spreading. The annual burden of visceral leishmaniasis (VL) in Ethiopia is estimated to be between 4,500 and 5,000 cases, and the population at risk is more than 3.2 million. There has been a change in the epidemiology of VL in Ethiopia. Over the last decades, almost all cases and outbreaks of VL were reported from arid and semi-arid parts of the country; however, recent reports indicated the introduction of this disease into the highlands. Migration of labourers to and from endemic areas, climatic and environmental changes, and impaired immunity due to HIV/AIDS and malnutrition resulted in the change of VL epidemiology. HIV spurs the spread of VL by increasing the risk of progression from asymptomatic infection towards full VL. Conversely, VL accelerates the onset of AIDS. In Ethiopia, VL epidemiology remains complex because of the diversity of risk factors involved, and its control is becoming an increasing challenge. This paper reviews the changes in epidemiology of VL in Ethiopia and discusses some of the possible explanations for these changes. The prospects for novel approaches to VL control are discussed, as are the current and future challenges facing Ethiopia's public health development program.